TCP/IP for dummies - Leiden, Candace; Wilensky, Marshall; Safari eBooks (Hoboken, N.J. : Wiley, 2009)
"TCP/IP is a hot topic, because it's the glue that holds the Internet and the Web together, and network administrators need to stay on top of the latest developments. TCP/IP For Dummies, 6th Edition, is both an introduction to the basics for beginners as well as the perfect go-to resource for TCP/IP veterans. The book includes the latest on Web protocols and new hardware, plus very timely information on how TCP/IP secures connectivity for blogging, vlogging, photoblogging, and social networking. Step-by-step instructions show you how to install and set up TCP/IP on clients and servers; build security with encryption, authentication, digital certificates, and signatures; handle new voice and mobile technologies, and much more"--Resource description page.
Description based on print version record.
Includes index.
Keywords: TCP/IP (Computer network protocol); Computer network protocols; Electronic books